Vendor density mapping and compliance assessment with tobacco control laws around schools in Bhubaneswar City—a geo-spatial mapping and observational study - Satpathy, Nancy; Jena, Pratap; Yadav, Amit; Epari, Venkatarao; Mohanty, Vikrant; Ali, Muhammad Imran; Khare, Rishika; Singh, Yogesh Pratap; Pandey, Ashish Kumar (Frontiers in Public Health, 2025)
BackgroundTobacco use among youth remains a significant public health challenge, particularly in India, where vendor accessibility plays a crucial role in initiation and consumption. This study examines tobacco vendor density around schools in Bhubaneswar City, Odisha, utilizing advanced geo-spatial mapping techniques to provide evidence for regulatory enforcement.MethodsA geo-spatial mapping approach was employed using ArcMap 10.8 and Google Maps to identify tobacco vendors within a 100-yard radius of 15 selected high schools. Data collection was conducted through a structured questionnaire with 53 closed-ended questions via the Epicollect5 platform. The study adopted a probability proportional-to-size sampling method to ensure representative vendor distribution.ResultsThe study identified 107 tobacco vendors surrounding the selected schools, with an average vendor density of approximately seven per school vicinity. Pan vendors and grocery/convenience stores were the most prevalent vendor types. Despite existing regulations, widespread tobacco advertising, brand displays, and promotional activities were observed. Additionally, violations related to smoking near schools and sales to minors indicated gaps in regulatory compliance.ConclusionThe high density of tobacco vendors near schools underscores the need for strengthened enforcement mechanisms and policy interventions. Enhancing regulatory compliance through stricter zoning laws, targeted monitoring, and community-driven initiatives is essential to reducing youth exposure to tobacco products and mitigating associated health risks.